Covid-19 pandemic and quality of life in entrepreneurs in the gastronomic sector of Huancayo city, 2021. - Ponce Romero , Giancarlo Giovanni (2022)
In the last year, all businesses were affected by the COVID-19 pandemic, unable to carry out their usual activities. Causing various problems in most entrepreneurs. The research has an objective to analyze the relationship between the COVID-19 pandemic and the quality of life in entrepreneurs in the gastronomic sector of the Huancayo district, 2021. The scientific method was used as a material and method with a quantitative approach and based on the For the purpose of the project, the descriptive correlational type was applied, the same one that had the purpose of showing or examining the relationship that exists between the study variables. Within the results obtained, we can affirm with respect to the general hypothesis that it was accepted because the value obtained from Spearman's rho correlation coefficient = -0.714 evidencing the existence of a mean inverse relationship between the COVID-19 pandemic and the quality of life in entrepreneurs in the gastronomic sector of the Huancayo district, 2021. With respect to the specific hypotheses, mean inverse relationships of -0.699, -0.674 and -0.736 are established between the independent variable and the study dimensions of the dependent variable (physical well-being, emotional well-being and personal and professional development). It is within this context that the conclusions show that the main challenge for all entrepreneurs in this sector, the same ones who already have a diminished quality of life due to the pandemic caused by COVID-19, is to seek permanence and development of their organizations within a rather adverse market. The research concludes that there is a mean inverse relationship between the study variables.